RESEÑA DE : Guinea Fernández, David Rafael. La declaración de fallecimiento en el Derecho español . Madrid : La Ley, 2011. - Moretón Sanz, M.ª Fernanda (Revista de Derecho de la UNED (RDUNED), 2013)
-